Budaya Media Sosial, Edukasi Masyarakat, dan Pandemi COVID-19 - Muchammad Bayu Tejo Sampurno; Tri Cahyo Kusumandyoko; Muh Ariffudin Islam (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis study wants to explore the public education of COVID-19 through the social and cultural media in it. Furthermore, this research also identifies how the media affect the community and by involving mass media communication in strategies to raise awareness about COVID-19 prevention and prevention efforts. This study uses a qualitative method by utilizing a virtual ethnographic approach that refers to the ethnographic research approach conducted in online settings about the internet and social media. The results show that social media culture in Indonesia can act as a teacher who can educate the public and stimulate in the latest research related to COVID-19; as education for public health services; directing people to their websites and landing pages for information on the latest and most trusted COVID-19; marketing innovative services such as health care social funding services; posts related to case information, photos, and results (with permission) relating to COVID-19 to educate the public; sharing reviews and testimonies of patients who recover as motivation and initial prevention efforts; and providing support among Indonesian citizens in the face of the COVID-19 pandemic.Keywords: Social Media Culture, Public Education, Covid-19 Pandemic AbstrakPenelitian ini ingin mengeksplorasi tentang edukasi masyarakat terhadap COVID-19 melalui media sosial dan budaya yang ada di dalamnya. Lebih lanjut, penelitian ini turut mengidentifikasi bagaimana media mempengaruhi masyarakat dan dengan melibatkan komunikasi media massa dalam strategi untuk meningkatkan kesadaran tentang usaha penanganan dan pencegahan COVID-19. Penelitian ini menggunakan metode kualitatif dengan memanfaatkan pendekatan virtual etnografi yang mengacu pada pendekatan penelitian etnografi yang dilakukan dalam pengaturan online tentang internet dan media sosial. Hasil penelitian menunjukkan bahwa budaya media sosial di Indonesia dapat bertindak sebagai guru yang mampu mengedukasi masyarakat dan menstimulasi dalam penelitian terbaru terkait COVID-19; sebagai pendidikan layanan kesehatan masyarakat; mengarahkan masyarakat ke situs web dan halaman arahan mereka untuk informasi terkait COVID-19 terbaru dan terpercaya; memasarkan layanan inovatif seperti layanan dana sosial perawatan kesehatan; posting terkait informasi kasus, foto, dan hasil (dengan izin) yang berkaitan dengan COVID-19 untuk mengedukasi masyarakat; berbagi ulasan dan testimoni pasien yang sembuh sebagai motivasi dan upaya awal pencegahan; dan memberikan dukungan antar warga negara Indonesia dalam menghadapi pandemi COVID-19.Kata kunci: Budaya Media Sosial, Edukasi Masyarakat, Pandemi Covid-19